2007
DOI: 10.1093/cercor/bhl174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Syllabic Lengthening on Semantic Processing in Spoken French: Behavioral and Electrophysiological Evidence

Abstract: The present work investigates the relationship between semantic and prosodic (metric) processing in spoken language under 2 attentional conditions (semantic and metric tasks) by analyzing both behavioral and event-related potential (ERP) data. Participants listened to short sentences ending in semantically and/or metrically congruous or incongruous trisyllabic words. In the metric task, ERP data showed that metrically incongruous words elicited both larger early negative and late positive components than metri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
113
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(135 citation statements)
references
References 55 publications
18
113
4
Order By: Relevance
“…The N400 rhyme effects in poetry are in line with previously reported auditory rhyme effects in common language (e.g., Coch et al, 2005;Davids et al, 2011;Praamstra et al, 1994;Praamstra & Stegeman, 1993). Similarly, the meter effect is in accordance with previous N400 and P600 findings concerning how regular meter facilitates auditory lexical, semantic, and syntactic sentence processing (for the N400, see, e.g., Bohn et al, 2013;Magne et al, 2007Magne et al, , 2010Rothermich et al, 2010Rothermich et al, , 2012; for the P600, see, e.g., Roncaglia-Denissen et al, 2013;Schmidt-Kassow & Kotz, 2009b; for both the N400 and P600, see Luo & Zhou, 2010;Marie et al, 2011;McCauley et al, 2013;Ystad et al, 2007). The present results also align well with the results of Bohn et al Those authors reasoned that irregular but possible metrical stress in spoken language enhances processing costs, whereas regular meter reduces processing costs.…”
Section: Ease Of Processing Is Enhanced By Poetic Language Usesupporting
confidence: 91%
See 2 more Smart Citations
“…The N400 rhyme effects in poetry are in line with previously reported auditory rhyme effects in common language (e.g., Coch et al, 2005;Davids et al, 2011;Praamstra et al, 1994;Praamstra & Stegeman, 1993). Similarly, the meter effect is in accordance with previous N400 and P600 findings concerning how regular meter facilitates auditory lexical, semantic, and syntactic sentence processing (for the N400, see, e.g., Bohn et al, 2013;Magne et al, 2007Magne et al, , 2010Rothermich et al, 2010Rothermich et al, , 2012; for the P600, see, e.g., Roncaglia-Denissen et al, 2013;Schmidt-Kassow & Kotz, 2009b; for both the N400 and P600, see Luo & Zhou, 2010;Marie et al, 2011;McCauley et al, 2013;Ystad et al, 2007). The present results also align well with the results of Bohn et al Those authors reasoned that irregular but possible metrical stress in spoken language enhances processing costs, whereas regular meter reduces processing costs.…”
Section: Ease Of Processing Is Enhanced By Poetic Language Usesupporting
confidence: 91%
“…Moreover, meter plays an important role in language acquisition (e.g., Jusczyk, 1999), as well as syntactic (e.g., SchmidtKassow & Kotz, 2009b) and semantic (e.g., Magne et al, 2007;Rothermich, Schmidt-Kassow, & Kotz, 2012) auditory language processing. Various studies have reported that the N400 response to single words and to words in sentences is reduced when the words are presented in a metrically regular context (e.g., Bohn, Knaus, Wiese, & Domahs, 2013;Magne, Gordon, & Midha, 2010;Magne et al, 2007;Rothermich et al, 2012;Rothermich, Schmidt-Kassow, Schwartze, & Kotz, 2010). For example, Magne et al (2007) investigated how regular meter influences semantic processing in spoken French.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, specific eventrelated brain potentials, the ''closure positive shift'' (CPS) or the P350, have been observed to be modulated by the processing of speech accent or speech pauses (Friedrich, Kotz, Friederici, & Alter, 2004;Steinhauer, Alter, & Friederici, 1999). Furthermore, a recently published study has reported an increased N400 for sentences comprising a syllable lengthening in the last word (Magne et al, 2007). However, to our knowledge, the perception of speech rhythm as a composition of the mentioned suprasegmental characteristics and expanding over a longer period of time, such as the duration of a sentence, has never been the subject of investigation in functional brain research.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was demonstrated that either an elongated or shortened single vowel in a recorded utterance could cause a perceptible momentary alteration and therefore listeners respond less quickly in a phoneme-monitoring task (Martin, 1979). Magne and colleagues obtained a similar result on normal adults: lexical access is impaired by metric incongruity on the word in a lexical decision task (Magne et al, 2007). Cutler et al (1997) interpreted this result as a momentary disruption of recognition arising from manipulations of the speech signal that makes listeners' predictions about temporal patterns wrong.…”
Section: Rhythm In Speech Comprehensionmentioning
confidence: 92%